Ultrastructural analysis of prostate cancer tissue provides insights into androgen-dependent adaptations to membrane contact site establishment - Butler, Lisa M.; Evergren, Emma (Frontiers in Oncology, 2023)
Membrane trafficking and organelle contact sites are important for regulating cell metabolism and survival; processes often deregulated in cancer. Prostate cancer is the second leading cause of cancer-related death in men in the developed world. While early-stage disease is curable by surgery or radiotherapy there is an unmet need to identify prognostic biomarkers, markers to treatment response and new therapeutic targets in intermediate-late stage disease. This study explored the morphology of organelles and membrane contact sites in tumor tissue from normal, low and intermediate histological grade groups. The morphology of organelles in secretory prostate epithelial cells; including Golgi apparatus, ER, lysosomes; was similar in prostate tissue samples across a range of Gleason scores. Mitochondrial morphology was not dramatically altered, but the number of membrane contacts with the ER notably increased with disease progression. A threefold increase of tight mitochondria-ER membrane contact sites was observed in the intermediate Gleason score group compared to normal tissue. To investigate whether these changes were concurrent with an increased androgen signaling in the tissue, we investigated whether an antiandrogen used in the clinic to treat advanced prostate cancer (enzalutamide) could reverse the phenotype. Patient-derived explant tissues with an intermediate Gleason score were cultured ex vivo in the presence or absence of enzalutamide and the number of ER-mitochondria contacts were quantified for each matched pair of tissues. Enzalutamide treated tissue showed a significant reduction in the number and length of mitochondria-ER contact sites, suggesting a novel androgendependent regulation of these membrane contact sites. This study provides evidence for the first time that prostate epithelial cells undergo adaptations in membrane contact sites between mitochondria and the ER during prostate cancer progression. These adaptations are androgendependent and provide evidence for a novel hormone-regulated mechanism that support establishment and extension of MAMs. Future studies will determine whether these changes are required to maintain pro-proliferative signaling and metabolic changes that support prostate cancer cell viability.